Effect of Nitriding Temperature and Time with Gas Mixture of 95% Nitrogen and 5% Hydrogen on MgAZ91D Alloy - Wan Azaha, Wan Nor Suhaina (IRC, 2018)
Magnesium alloy is a low-density material that widely used in the automotive and telecommunication industries. However, it has low surface hardness and low creep resistance which restrict their broader engineering applications. This project is concerned about the improvement of magnesium alloy, MgAZ91D mechanical properties after gas mixture 95% nitrogen and 5% hydrogen of nitriding with different temperature and time were applied. The magnesium alloy, MgAZ91D was exposed into the gas mixture nitriding at 300 o C, 350 o C, 400 o C, 450 o C and 500 o C in a tube furnace for a period of 1 and 2 hours respectively. The condition and distribution of the gas mixture nitriding were observed using Energy-Dispersive X-ray Spectroscopy (EDX). Analysis of the surface hardness of the material is conducted by using two methods of testing which they are Vickers hardness test and surface roughness test. Both methods are observed by using a calibrated machine for hardness and profilometer. Many papers discussed that the mechanical properties will be altered when heat treatment on a material is executed. By accomplishing this project, it will develop magnesium alloy, MgAZ91D to have better mechanical properties especially the surface hardness and improve the restriction of MgAZ91D in engineering applications.